2017
DOI: 10.1002/hon.2388
|View full text |Cite
|
Sign up to set email alerts
|

The use of BRAF V600E mutation‐specific immunohistochemistry in pediatric Langerhans cell histiocytosis

Abstract: BRAF p.V600E mutations are detected in greater than 50% of pediatric Langerhans cell histiocytosis (LCH) lesions. However, the use of mutation-specific BRAF V600E immunohistochemistry (IHC) as a surrogate for molecular testing in pediatric LCH is unknown. We tested the mutation-specific BRAF V600E monoclonal antibody (clone VE1) in formalin-fixed, paraffin-embedded LCH samples from 26 pediatric patients (14 males and 12 females, ages 7 mo-17 y) using allele-specific real-time polymerase chain reaction (PCR) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…Although many studies have shown that IHC has a good detection effect on BRAF V600E mutations ( 29 32 ), but there will still be a part of false positive results ( 33 , 34 ). Ballester et al ( 35 ) suggested that the highly sensitive molecular assays remain the gold standard for BRAF mutation analysis in paraffin-embedded lesions. Ehsani et al ( 36 ) used IHC to detect BRAF mutations in metastatic malignant melanoma with a false positive rate of 32%.…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have shown that IHC has a good detection effect on BRAF V600E mutations ( 29 32 ), but there will still be a part of false positive results ( 33 , 34 ). Ballester et al ( 35 ) suggested that the highly sensitive molecular assays remain the gold standard for BRAF mutation analysis in paraffin-embedded lesions. Ehsani et al ( 36 ) used IHC to detect BRAF mutations in metastatic malignant melanoma with a false positive rate of 32%.…”
Section: Discussionmentioning
confidence: 99%
“…The BRAF V600E mutation may be robustly detected using immunohistochemistry using the clone VE1 on formalin-fixed paraffin-embedded tissue [64], while future diagnosis of LCH could achieved by detecting mutations in circulating DNA using liquid biopsy.…”
Section: Langerhans Cell Histiocytosis and Other Histiocytic Disordersmentioning
confidence: 99%
“…However, BRAF immuno- histochemistry for BRAF V600E mutation has been reported to have low sensitivity and specificity in LCH or other histiocytic and dendritic cell neoplasms. [29][30][31] Therefore, further validation is required to elucidate the accuracy of immunohistochemistry in determining BRAF V600E mutation status in histiocytic and dendritic cell neoplasms. Our outcome analyses showed that most of the histiocytic and dendritic cell neoplasms exhibit indolent clinical behaviours.…”
Section: Discussionmentioning
confidence: 99%